GIS-material for the archaeological project: From Ringeby to Ljura - Arkeologikonsult (Arkeologikonsult, 2014)
The information in the abstract is translated from the archaeological report:
During early fall 2008, Arkeologikonsult performed an archaeological assessment (stage 1) in an area from the Ingelstad junction via Händelö to the Ljura junction outside Norrköping. The assessment was carried out as decided by the County Administrative Board in Östergötland, as a reslut of the planning before the construction of E22 Norrleden in Norrköping municipality. The investigated area comprised about 450 ha.The aim was to explore the existence of ancient monuments and ancient environments, and to clarify the area's historical character and antiquarian history. The assessment showed that there are several archaeological and cultural monuments in and adjacent to the study area, and that there are several areas with topographically suitable settlement and burial locations. Within the study area a total of 15 sites were identified.

Purpose:

The information in the purpose is translated from the archaeological report:
The goal of the archaeological assessment was to explore the existence of ancient monuments and archaeological areas in the study area. This included both identifying the visible archaeological and cultural remains, as well as areas in which the possibility is high that legally protected monuments without visible markings above ground may exist. These sites and areas were mapped and described. Furthermore the assessment aimed at providing suggestions for further archaeological work in the area.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Under tidig höst 2008 utförde Arkeologikonsult en arkeologisk utredning (etapp 1) inom ett område från Ingelstad trafikplats via Händelö till Ljura trafikplats utanför Norrköping. Utredningen genomfördes enligt beslut av länsstyrelsen i Östergötlands län med anledning av projektering inför byggande av väg E22 Norrleden i Norrköpings kommun. Utredningsområdet omfattade ca 450 hektar. Utredningen visade att det finns flera forn- och kulturlämningar i och intill utredningsområdet samt att det finns flera områden med topografiskt lämpliga boplats- och gravlägen. Inom utredningsområdet identifierades sammanlagt 15 objekt.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Målsättningen med den arkeologiska utredningen var att utforska förekomsten av fasta fornlämningar och fornlämningsmiljöer inom utredningsområdet. Detta innefattade ett påvisande av såväl synliga forn- och kulturlämningar, som områden inom vilka möjligheten är stor att lagskyddade lämningar utan synlig markering ovan jord kan finnas. Dessa lämningar och områden skulle inom ramen för utredningen karteras och beskrivas. Vidare syftade utredningen till att lämna förslag på fortsatta arkeologiska insatser inom området.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.

Utredningen genomfördes som en etapp 1, d v s utan att några ingrepp i marken gjordes, och kom att innefatta flera moment: - inledande arkiv-, litteratur- och kartstudier - inventering och kartering i fält - efterföljande rapportarbete med upprättande av rekommendationer om fortsatta antikvariska åtgärder
GIS-material för arkeologiskt projekt: Från Ringeby till Ljura
Keywords: History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive